PFM.47 Does Magnetic Resonance Imaging (MRI) of the fetal brain improve the accuracy of diagnosis for mild and severe ventriculomegaly?. (9th June 2014) - Lightly, K; Simms, R; Leibling, R; Overton, T; Denbow, M
Abstract : Aim: Pilot data from our unit suggested that MRI did not add information in isolated ventriculomegaly. 1 Therefore we aimed (i) to assess this in a larger series, and (ii) to examine the ability of modern ultrasound technologies to assess corpus callosum (CC) anomalies. Setting: A large UK tertiary referral unit. Methods: A retrospective review of all MRIs between 2008–2013 was carried out. In cases of ventriculomegaly (mild 10–15mm; severe 15mm+) ultrasound and MRI findings were compared. Results: In this period 121 MRIs were carried out, of these 65 had ventriculomegaly (full information in 64). Other common indications for MRI included multiples post IUD/TTTS and complex intracranial abnormalities. In 95% cases of ventriculomegaly (61/64), MRI confirmed ultrasound findings and did not add any further information. Agenesis of the corpus callosum was suspected in six cases with ventriculomegaly, and confirmed by MRI in four. There were no cases of agenesis of CC found unexpectedly at MRI where the indication was mild ventriculomegaly. Conclusion: Where ultrasound reveals isolated ventriculomegaly, MRI did not add any further information. When agenesis of the CC is suspected on ultrasound, an MRI is useful in confirming the diagnosis. Reference: Platt et al. Clinical value of fetal brain MRI; Indications and limitations. PF 18. Arch Dis Child Fetal Neonatal Ed 2009;94(Suppl):Fa11–Fa25